2010
DOI: 10.1590/s0004-282x2010000600013
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of SUDEP in a cohort of patients with refractory epilepsy: the role of surgery and lesion localization

Abstract: Objective: The aim of this study was to verify incidence and characteristics of sudden unexpected death in patients (SUDEP) with refractory epilepsy and its relation to previous surgery and lesion localization. Method: A cross sectional study was carried out in a cohort of 550 patients with refractory epilepsy followed up by the Epilepsy Surgery Program of the University Hospital of PUCRS, Porto Alegre, Brazil, between January, 1992 and July, 2002. Patients were allocated in two groups (operated and non operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 30 publications
0
29
0
1
Order By: Relevance
“…Confirming this finding our group demonstrated that patients with refractory epilepsy that became seizure free after epilepsy surgery had a lower SUDEP rate 22 . Other authors demonstrated a higher risk of SUDEP in patients with extratemporal epilepsy 23 . Although a higher mortality in boys had been reported 4,6 , we could not confirm that finding.…”
Section: Discussionmentioning
confidence: 90%
“…Confirming this finding our group demonstrated that patients with refractory epilepsy that became seizure free after epilepsy surgery had a lower SUDEP rate 22 . Other authors demonstrated a higher risk of SUDEP in patients with extratemporal epilepsy 23 . Although a higher mortality in boys had been reported 4,6 , we could not confirm that finding.…”
Section: Discussionmentioning
confidence: 90%
“…and two articles reported separate findings from the same cohort . Thus, the articles contained 12 reports of findings from population‐based cohorts and eight reports from clinical cohorts . South America provided eight studies, Asia six studies, and Africa six studies .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the articles contained 12 reports of findings from population‐based cohorts and eight reports from clinical cohorts . South America provided eight studies, Asia six studies, and Africa six studies . Nine studies were conducted in rural populations only, six in urban only, and five in both urban and rural populations …”
Section: Resultsmentioning
confidence: 99%
“…The SUDEP risk is closely related to the frequency of major convulsive seizures [1,39], but the literature on the relationship between meningioma and SUDEP is scarce. However, AEDs can also have adverse effects so the decision to treat, with what, and for how long needs to be based on a careful risk benefit analysis.…”
Section: Not Availablementioning
confidence: 99%